2023
DOI: 10.1136/bmjopen-2023-072994
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use among workers with work-related injuries and illnesses: results from a cross-sectional study of workers’ compensation claimants in Ontario, Canada

Abstract: ObjectivesLittle is known about how workers use cannabis following a work-related injury/illness, including whether they receive clinical guidance. The objective was to compare characteristics of workers using and not using cannabis after a work-related injury/illness and describe use patterns.DesignCross-sectional study.Setting and participantsWorkers who experienced a work-related physical injury/illness resulting in one or more days of lost time compensated by the workers’ compensation authority in Ontario,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…Unlike prior studies, which were mainly conducted more than 10 years ago, sleep and medical motives were also reported by almost a third of respondents, perhaps reflecting the growing public discourse on the therapeutic potential of cannabis [35,36]. A recent study conducted by our team also found that workers' compensation claimants often reported using cannabis to cope with stress and for relaxation, but those who reported using cannabis specifically for their injury and illness symptoms more often reported use for pain, sleep, and mental health [14]. While evidence to support the effectiveness of cannabis for physical and mental health continues to evolve [37], healthcare providers should be aware of these common motivations for use among their working patients in order to best counsel them on use.…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Unlike prior studies, which were mainly conducted more than 10 years ago, sleep and medical motives were also reported by almost a third of respondents, perhaps reflecting the growing public discourse on the therapeutic potential of cannabis [35,36]. A recent study conducted by our team also found that workers' compensation claimants often reported using cannabis to cope with stress and for relaxation, but those who reported using cannabis specifically for their injury and illness symptoms more often reported use for pain, sleep, and mental health [14]. While evidence to support the effectiveness of cannabis for physical and mental health continues to evolve [37], healthcare providers should be aware of these common motivations for use among their working patients in order to best counsel them on use.…”
Section: Discussionmentioning
confidence: 80%
“…Working adults, in particular, may experience various work-related circumstances that motivate them to use cannabis, such as high work stress, low job satisfaction, and long hours or irregular shifts [12]. Indeed, recent data suggests cannabis use is common in the working population [12][13][14][15][16]. However, little is known about why workers use cannabis.…”
Section: Introductionmentioning
confidence: 99%
“…The global increase in legal access to cannabis and cannabinoid-based products for medical and non-medical purposes has been paralleled by their widespread promotion and use. In particular, North America has the highest rate of cannabis use in the world, where some of the first jurisdictions to legalize cannabis exist [ 1 3 ]. In recent years, North America has been reported to have the highest prevalence of past-year cannabis use compared to other sub-regions globally at 14.5% [ 4 ].…”
Section: Introductionmentioning
confidence: 99%